Legal treatment of the victim-offender relationship in crimes of violence - Simon, L. M. J. (Journal of interpersonal violence, 1996)
Prior theory and research indicate that the victim-offender relationship is an important factor in determining how an offender is treated at various stages of the criminal justice system, with stranger offenders faring worse than nonstranger offenders in all stages of legal processing. This study investigates whether the victim-offender relationship plays a role in determining the original charge, the crime conviction, and the sentence length of inmates in prison for violent crimes. Data consist of interview and official record information of 273 sentenced and incarcerated violent male offenders. The results indicate that the victim-offender relationship is related to the legal processing, but in paradoxical ways. Thus, although nonstranger offenders are charged with and convicted of more serious crimes, stranger offenders receive significantly longer sentences. Implications for policy and future research are discussed